2021
DOI: 10.51791/njap.v43i1.2774
|View full text |Cite
|
Sign up to set email alerts
|

Growth, blood indices and carcass characteristics of japanese quail (Coturnix coturnix japonica) fed cassava grit as replacement for maize with or without β glucanase

Abstract: One hundred and eighty (180) unsexed twenty-one day-old growing Japanese quails (Coturnix coturnix japonica) were fed for 28 days with diets in which maize was replaced with cassava grit at 0, 25 and 50% with or without ß-glucanase supplementation. The birds were randomly grouped into six treatments in three replicates often birds per replicate. Diet 1 was the control without cassava grit while diets 2 and 3 had 25 and 50% of their maize contents replaced with cassava grit respectively. Diets 4, 5 and 6 were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…High level of ALP is suggestive of malnutrition, hence, it is not recommended to feed whole sorghum to quails, for reasons of low disease resistance, and poor feed, energy, and mineral utilization (Masenya et al, 2021). In another study, the inclusion of cassava grit in quail diet increased the red and white blood cells in quails and this might have been due to the influence of the experimental diet on the blood traits, which showed that birds that consumed the experimental diets were healthy (Oyelami and Abu, 2017).…”
Section: Effect Of Alternative Energy Sources On Blood Parametersmentioning
confidence: 99%
“…High level of ALP is suggestive of malnutrition, hence, it is not recommended to feed whole sorghum to quails, for reasons of low disease resistance, and poor feed, energy, and mineral utilization (Masenya et al, 2021). In another study, the inclusion of cassava grit in quail diet increased the red and white blood cells in quails and this might have been due to the influence of the experimental diet on the blood traits, which showed that birds that consumed the experimental diets were healthy (Oyelami and Abu, 2017).…”
Section: Effect Of Alternative Energy Sources On Blood Parametersmentioning
confidence: 99%